2023
DOI: 10.2147/mder.s398193
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Non-Invasive Brain Pulse Monitor to Measure Intra-Cranial Pressure Following Acute Brain Injury

Abstract: Background Intracranial pressure (ICP) monitoring requires placing a hole in the skull through which an invasive pressure monitor is inserted into the brain. This approach has risks for the patient and is expensive. We have developed a non-invasive brain pulse monitor that uses red light to detect a photoplethysmographic (PPG) signal arising from the blood vessels on the brain’s cortical surface. The brain PPG and the invasive ICP waveform share morphological features which may allow measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…The monitor has been described in detail previously. [22][23][24] In brief, the monitor uses near-infrared (NIR) light sources (660 and 940 nm). Each brain sensor has a single light-emitting diode (LED) and photodetector (PD).…”
Section: Brain Pulse Monitormentioning
confidence: 99%
See 2 more Smart Citations
“…The monitor has been described in detail previously. [22][23][24] In brief, the monitor uses near-infrared (NIR) light sources (660 and 940 nm). Each brain sensor has a single light-emitting diode (LED) and photodetector (PD).…”
Section: Brain Pulse Monitormentioning
confidence: 99%
“…[28][29][30][31] The PPG signal is feature-rich and allows estimation of blood flow, ICP, compliance and oxygen saturation. [22][23][24] Invasive ICP An extra-ventricular drain was placed in the right lateral ventricle. The pressure levels were zeroed at the tragus and monitored by a Philips IntelliVue system.…”
Section: Optical Intensity and Brain Pulse Waveformmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they found only a fair estimation of the ICP waveform in a third of their sample and did not recommend its use for clinical management [ 27 ]. More recently, Dixon et al [ 28 ] developed an algorithm using photoplethysmography to assess the correlation between morphological features of the photoplethysmography waveform and ICP levels. This study involved 24 simultaneous recordings in 12 patients with ABI without skin or skull injuries.…”
Section: Noninvasive Icp Monitoringmentioning
confidence: 99%
“…The authors observed a significant correlation between the morphology of the brain pulse wave and ICP levels ( R 2 = 0.66, p = 0.001). However, further validation studies with larger and preferably blinded samples are needed to confirm these findings [ 28 ].…”
Section: Noninvasive Icp Monitoringmentioning
confidence: 99%